Relationship between Inflammation and Oxidative Stress and Cognitive Decline in the Institutionalized Elderly. (19th March 2015) - Baierle, Marília; Nascimento, Sabrina N.; Moro, Angela M.; Brucker, Natália; Freitas, Fernando; Gauer, Bruna; Durgante, Juliano; Bordignon, Suelen; Zibetti, Murilo; Trentini, Clarissa M.; Duarte, Marta M. M. F.; Grune, Tilman; et al.
Abstract : Objective . Cognitive impairment reduces quality of life and is related to vascular and neurodegenerative disorders. However, there is also a close relationship between these diseases and oxidative stress. Thus, the purpose of this study was to assess whether inflammation and oxidative damage are associated with low cognitive performance in the elderly with different housing conditions. Methods . The study groups consisted of 32 institutionalized and 25 noninstitutionalized Brazilian elderly subjects. Oxidative damage, inflammation markers, and cognitive function were evaluated. Results . The results demonstrated pronounced oxidative stress in the institutionalized elderly group, which also had a lower antioxidant status compared to noninstitutionalized subjects. High levels of proinflammatory cytokines were also observed in the institutionalized elderly. Furthermore, the raised levels of inflammatory markers were correlated with increased oxidative stress, and both were associated with low cognitive performance. However, based on multiple linear regression analysis, oxidative stress appears to be the main factor responsible for the cognitive decline. Conclusions . The findings suggest that individuals with lower antioxidant status are more vulnerable to oxidative stress, which is associated with cognitive function, leading to reduced life quality and expectancy.